Cutting Edge Preclinical Models in Translational Medicine - Attanasio, Chiara (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In vitro, in vivo, and in silico preclinical models hold a widely acknowledged potential, yet complex limitations. For this reason, which has been known for a long time by experimenters and modelers, the translation of "science products" to the clinic is still far. Therefore, there is a raising awareness of the need to bridge this gap by developing integrated and innovative models. Organ and tissue bioengineering is an ideal approach to foster innovative strategies in significant research and clinical areas. Similarly, in translational neuroscience research, this challenge has been taken up by intriguing fish models. However, much research based on novel methodologies has still to be performed to get the bench closer to the bedside.